Climate Change Diplomacy: Towards Sustainable Global Cooperation - Diah Apriliani; Dina Dina (Social Studies and Humanities Journal (SOSHUM), 2024)
In this research, researchers conducted a systematic literature review to examine conceptualization, political, economic and cultural factors, and their relationship in climate change diplomacy. Various studies and publications were explored from various international journals indexed by Scopus Q1. It was found that climate change diplomacy is a complex process involving various factors at the national and international levels. Political, economic and cultural factors have a significant role in shaping sustainable global cooperation in overcoming the challenge of climate change. The implication of this research is the need for a deep understanding of these factors to develop effective diplomatic strategies in dealing with global climate change.